Harmonic Testing Analysis of Light Emitting Diode (LED) Lamps based SNI IEC 61000-3-2 Standard. Issue 1 (February 2021) - Wibowo, R; Suryadi; Priambodo, P S
Abstract: The use of LED lamps in Indonesia has increased since 2013 because of low power consumption and high efficiency. LED lamps are non-linear loads that cause harmonic distortion in the electric power system. Harmonic distortion can impact to overheating in magnetic core electrical equipment. Therefore, it is necessary to standardize the limits of the harmonic emission limits of LED lamps. In this study, the harmonics measurements of LED lamps of 22 samples from 10 brands, which include different types of EMI filters in the LED drivers, are carried out to analyze harmonic currents. Measurements in this study conducted using Teseq ProfLine 2105. The results of parameter testing of third and fifth-order harmonic currents, peak current phase angle, beginning current flow at 60 degrees, and end current at 90 degrees were analyze based on the criteria for class C SNI IEC 61000-3-2 standard. The results showed that the three samples used EMI filter inductor in the LED driver can minimize third-order harmonic currents and comply with all parameters.